German Literature in the Age of Globalisation. - Taberner, Stuart (Bloomsbury Publishing, 2004)
Literary fiction in Germany has long been a medium for contemplation of the ''nation'' and questions of national identity. From the mid-1990s, in the wake of heated debates on the future direction of culture, politics and society in a more ''normal'', united country, German literature has become increasingly diverse and seemingly disparate - at the one extreme, it represents the attempt to ''reinvent'' German traditions, at the other, the unmistakable influence of Anglo-American forms and pop literature. A shared concern of almost all of recent German fiction, however, is the contemporary deba.